When do workers actually deactivate from the labour market? Non-routine transition from unemployment to retirement - Gałecka-Burdziak, Ewa; Góra, Marek (Studia Demograficzne, 2025)
The paper investigates the labour force attachment patterns of older workers up to six years prior to transitioning from registered unemployment to retirement. In the study we have identified periods of (un)employment and non-participation, applied sequence analysis and estimated a k-progressive competing risk multi-state model. We used administrative data from public employment offices in Poland referring to the entire population of workers born between 1940 and 1965 who retired directly from unemployment between 2001 and 2017. Our finding is that, on average, 81% of all the observation time was spent in non-employment, and mostly in prolonged unemployment spells. Rates of unemployment were higher the closer workers were to their retirement. These workers tended to collect unemployment benefits as long as possible, and only 43% spent any time in employment during the observation period. Thus, it appears that these workers restricted their labour market activity while waiting to acquire pension benefit rights.